Population living on permafrost in the Arctic - Ramage, Justine; Jungsberg, Leneisja; Wang, Shinan; Westermann, Sebastian; Lantuit, Hugues (Prof. Dr.); Heleniak, Timothy (Population and Environment, 2021)
Permafrost thaw is a challenge in many Arctic regions, one that modifies ecosystems and affects infrastructure and livelihoods. To date, there have been no demographic studies of the population on permafrost. We present the first estimates of the number of inhabitants on permafrost in the Arctic Circumpolar Permafrost Region (ACPR) and project changes as a result of permafrost thaw. We combine current and projected populations at settlement level with permafrost extent. Key findings indicate that there are 1162 permafrost settlements in the ACPR, accommodating 5 million inhabitants, of whom 1 million live along a coast. Climate-driven permafrost projections suggest that by 2050, 42% of the permafrost settlements will become permafrost-free due to thawing. Among the settlements remaining on permafrost, 42% are in high hazard zones, where the consequences of permafrost thaw will be most severe. In total, 3.3 million people in the ACPR live currently in settlements where permafrost will degrade and ultimately disappear by 2050.